NARASI KAUM MISKIN: KARAKTER AGEN PASTORAL - Hubertus Muda (STIPAS St. Sirilus Ruteng, 2014)
The poor are those who are (1) materally impowerished; (2) economically and politicallypowerless, and (3) cognizant oftheir own weakness, looking to God for help since thay cannot find it anywhere else. Theologically, it can be said that in the old testament the mere fact of poverty laid a heavy responsibility on the non-poor, an obligation which was demanded by the law and not left to the goodwill ofthe individual. This article made it clear that social responsibility for the poor and the oppressed belonged to the Covenantand took priority over worship God has a particular love for the poor and disadvantaged in society and he would stand up for them Jesus critique is not based on a comparison of doctrine and teachings. His critique is not a theoretical exercise, as is often the case with cathechists. It is this God of compassion that Jesus tried to reintroduced to the followers of him. He wants the teachers of the church to gain their faith in such a God. He did not do byconstructing a doctrine of God but by telling the story of the good samaritan.What he said was: